Fabrication of AIE-active amphiphilic fluorescent polymeric nanoparticles through host–guest interaction. Issue 60 (7th June 2016) - Chen, Junyu; Luo, Songsong; Xu, Dazhuang; Xue, Yun; Huang, Hongye; Wan, Qing; Liu, Meiying; Zhang, Xiaoyong; Wei, Yen
Abstract : Novel polymeric luminescent nanoprobes with aggregation induced emission (AIE) properties were fabricated via host–guest interaction between the β-CD pendant copolymers and adamantane-terminated AIE dye. Abstract : Fluorescent polymeric nanoparticles (FPNs) have obtained more and more attention in recent years due to their excellent performance in the fields of bioimaging, biosensing, theranostics and many other biomedical applications. In this work, we reported a novel method to fabricate amphiphilic fluorescent copolymers through host–guest interactions based on an aggregation-induced emission (AIE) active dye (named as Ad-PhNH2 ) and β cyclodextrin (β-CD) contained polymers, which were synthesized by free radical polymerization and subsequent ring-opening reaction. These AIE active copolymers can self assemble into FPNs (named as PEGMA–IA–β-CD/Ad-PhNH2 ) due to their amphiphilic properties. The hydrophobic dye was aggregated in the core and therefore can emit strong fluorescent intensity due to its AIE feature. However, the hydrophilic polymers that covered the hydrophobic core can endow good dispersibility in pure aqueous solution. Biological evaluation results demonstrated that PEGMA–IA–β-CD/Ad-PhNH2 FPNs can be effectively internalized into cells and they have shown low cytotoxicity. More importantly, the molar ratio of β-CD to Ad-PhNH2 can be facilely adjusted and the surplus β-CD can be used for carrying chemical anticancer agents. Furthermore, a large number of carboxyl groups were generated during the ring opening reaction. These negative carboxyl groups can be potentially used for further conjugation reactions and for biological delivery. The above described features of PEGMA–IA–β-CD/Ad-PhNH2 FPNs make them a prospect in biological imaging and delivery applications.